Model Matematika Penyebaran Mikroplastik di Laut Tropis Indonesia - Yani Pratiwi; Siti Saharah Abdullah (CV. Aksara Global Akademia, 2024)
Microplastics have emerged as a serious threat to tropical marine ecosystems in Indonesia, particularly in coastal areas with dense populations, major river estuaries, and busy shipping routes. This study aims to develop a predictive model of microplastic dispersion using partial differential equations based on ocean current data. The data set includes ocean currents derived from satellite imagery, global oceanographic models, and field observations, combined with information on microplastic sources from coastal human activities. The modeling process was conducted through numerical simulations using the finite difference method, taking into account geographic boundary conditions and numerical stability. The results indicate that the spatial distribution of microplastics is strongly influenced by seasonal current patterns closely associated with the Asian-Australian monsoon system. Microplastic concentrations tend to increase in areas with closed circulation and complex marine topography, with the highest accumulation identified in the Makassar Strait and the Java Sea. These findings highlight the critical role of ocean currents and other oceanographic factors in governing the transport and accumulation of microplastics in tropical seas. Ecologically, the outcomes suggest serious risks for coastal ecosystems, marine biodiversity, and the fisheries sector that supports Indonesia’s coastal communities. The implications of this study emphasize the need for more comprehensive marine environmental management strategies, strengthened field monitoring, and the integration of scientific models into plastic pollution control policies.